Effect of processing variables on the physico-chemical characteristics and aroma of borş, a traditional beverage derived from wheat bran. (1st November 2018) - Pasqualone, Antonella; Summo, Carmine; Laddomada, Barbara; Mudura, Elena; Coldea, Teodora Emilia
Highlights: Borş is a traditional fermented Romanian cereal-based beverage. Physico-chemical components and aroma profile of borş were studied. Total phenolics, ferulic acid, and antioxidant activity increased by using a starter. High fermentation temperature raised phenolics, brownness and antioxidant activity. Volatile compounds and pungent-sour odor increased at higher fermenting temperature. Abstract: Borş is a traditional Romanian beverage obtained by naturally fermenting an aqueous suspension of wheat bran and corn flour, used as flavoring enhancer in local gastronomy since ancient times, and more recently consumed as refreshing drink. To investigate the changes in sensory, physico-chemical, phenolic and aroma composition resulted after two successive fermentations, borș samples were subjected to standard, sensory, HPLC and GC/MS analysis. Total phenolic compounds and ferulic acid, the most abundant phenolic compound, were positively influenced by natural starter addition, increase of fermentation temperature, and thermal treatment, whereas the effect on less abundant phenolic acids was not univocal. The variables had the same effect on antioxidant activity and brown index. Volatiles (alcohols, carboxylic acids, esters), pungent-sour and goat milk-cheese odor notes increased at higher fermentation temperature, whereas bran and yogurt odor notes decreased. The addition of a natural starter at 4 °C allowed balancing odor intensity and antioxidant activity.